2021
DOI: 10.1017/s1431927620024964
|View full text |Cite
|
Sign up to set email alerts
|

Histone Demethylase KDM4D Could Improve the Developmental Competence of Buffalo (Bubalus Bubalis) Somatic Cell Nuclear Transfer (SCNT) Embryos

Abstract: Somatic cell nuclear transfer (SCNT) holds vast potential in agriculture. However, its applications are still limited by its low efficiency. Histone 3 lysine 9 trimethylation (H3K9me3) was identified as an epigenetic barrier for this. Histone demethylase KDM4D could regulate the level of H3K9me3. However, its effects on buffalo SCNT embryos are still unclear. Thus, we performed this study to explore the effects and underlying mechanism of KDM4D on buffalo SCNT embryos. The results revealed that compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…These genes function mainly in the regulation of the H3K9 locus and DNA methylation, which is consistent with previous findings that found the reprogramming blocking region to be enriched by H3K9me3 [14]. Furthermore, it has been discovered that a high expression of the demethylase KDM4D/E of H3K9me3 significantly improves cloning efficiency and birth rate in various animals [24][25][26]. It is yet to be determined whether the overall efficiency can be synergistically enhanced by using UC-MSCs as nucleus donors followed by a high expression of KDM4D/E.…”
Section: Discussionsupporting
confidence: 90%
“…These genes function mainly in the regulation of the H3K9 locus and DNA methylation, which is consistent with previous findings that found the reprogramming blocking region to be enriched by H3K9me3 [14]. Furthermore, it has been discovered that a high expression of the demethylase KDM4D/E of H3K9me3 significantly improves cloning efficiency and birth rate in various animals [24][25][26]. It is yet to be determined whether the overall efficiency can be synergistically enhanced by using UC-MSCs as nucleus donors followed by a high expression of KDM4D/E.…”
Section: Discussionsupporting
confidence: 90%
“…It is reported that abnormal DNA methylation can also inhibit the differentiation of human embryonic stem cells by inhibiting the expression of pluripotency genes (33). In addition, H3K9me3 and DNA methylation modification levels are also associated with DNA damage repair in embryonic development, and their abnormal elevation can increase DNA damage in embryonic development and inhibit the expression of ZGA genes (18,34,35). But it is unclear whether ELF4 regulates epigenetic modifications in porcine embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ZGA is involved in multiple epigenetic modifications that are critical for preimplantation development ( 17 ). It is reported that abnormally high levels of H3K9me3 in mammalian somatic cell nuclear transfer (SCNT) embryos are an epigenetic barrier to reprogramming and the levels of histone demethylase KDM4D can regulate the levels of abnormal H3K9me3 in ZGA-stage embryos ( 18 , 19 ). Greenberg et al found an inverse relationship between promoter methylation and gene expression during mammalian preimplantation embryonic development, suggesting a suppressive effect of DNA methylation on embryonic development ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…In SCNT buffalo embryos, the expression level of Kdm4d was significantly lower while the level of H3K9me3 was significantly higher when compared with the IVEP buffalo embryos. Microinjection of Kdm4d mRNA could correct the H3K9me3 level, increase the expression level of ZGA ( ZSCAN5B , SNAI1 , eIF‐3a , and TRC ) and pluripotency‐related genes ( POU5F1 , SOX2 , and NANOG ) and promote the developmental ability of buffalo SCNT embryos (Feng et al, 2021 ). Events of epigenetic modification such as histone acetylation, DNA methylation, and histone methylation should be deeper studied during buffalo embryonic development.…”
Section: Scntmentioning
confidence: 99%